The Contribution of Wahhabis to the Independence of the Republic of Indonesia - Riswandi Riswandi; St. Maisyah Nur Ali; Elza Ramona; Ahmad Faturrahman; Mirwan Mirwan; Murdifin Murdifin (Journal Social Civilecial, 2026)
This study examines the role of the Wahhabi-inspired Islamic reform movement in resisting colonialism and contributing to the Indonesian independence movement, particularly in Minangkabau, West Sumatra. The research aims to analyze the forms of struggle carried out by reformist Islamic groups from the Padri movement in the nineteenth century to the emergence of modern Islamic educational and political organizations in the early twentieth century. This study employs a qualitative historical research method using a library research approach. Data were collected from books, journals, historical documents, archives, newspapers, and other relevant literature, and analyzed through historical, political, sociological, and theological approaches. The findings show that the movement initially emerged as a religious purification movement emphasizing the return to Islamic teachings based on the Qur’an and Sunnah while opposing practices considered inconsistent with Islam. However, Dutch colonial intervention transformed the movement into broader anti-colonial resistance. The Padri movement under the leadership of Tuanku Imam Bonjol became an important symbol of armed resistance against Dutch expansion in West Sumatra. After the military defeat of the Padri movement, reformist ideas continued through educational, intellectual, and political movements led by figures such as Sheikh Ahmad Khatib al-Minangkabawi and Sheikh Taher Jalaluddin al-Azhari. Organizations and institutions such as Sumatra Thawalib, PMI, and PERMI played significant roles in strengthening Islamic consciousness, educational reform, and nationalist awareness among Indonesian Muslims. The study concludes that the Wahhabi-inspired reform movement contributed significantly to Indonesia’s independence through military, educational, intellectual, social, and political transformation.